L’Homme espagnol : une entrée dans l’histoire des mentalités - Isabelle Poutrin (Les Cahiers de Framespa)
The article situates L’Homme espagnol (1975) by Bartolomé Bennassar in the historiographical and political context of the 1970’s and in its author’s carrier. Pointing out the interesting elements of the book, it looks with a critical eye the body of evidence used by Bennassar, as well as his vision of Spanish Catholicism and of the women’s role, issues that recent research has largely renewed.